1970
DOI: 10.3329/dujps.v5i1.219
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Application of a Modified RP-HPLC Method for the Quantification of Desloratadine in Pharmaceutical Dosage Forms

Abstract: ABSTRACT:The purpose of the study was to develop a simple, sensitive and rapid RP-HPLC method for the determination of desloratadine in marketed products. Chromatographic determination was performed in a reverse phase C 18 column (250 mm × 3.3 mm I.D. , 5µm particle size) using a mixture of acetonitrile ‫׃‬ n-pentane sulphonic acid sodium salt monohydrate, adjusted to pH 3.0± 0.05 with phosphoric acid ‫׃06(‬ 40 v/v) as mobile phase and delivered at a flow rate of 1 ml/min. The UV detection was set at 254 nm. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Desloratadine is chemically 8-chloro-6,11-dihydro-11-(4-piperidinylidene)-5H-benzo [5,6] cyclohepta [1,2-b] pyridine is a antihistaminic drug. Desloratadine is an non-sedative antihistaminic drug with selective H1receptor antagonist activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desloratadine is chemically 8-chloro-6,11-dihydro-11-(4-piperidinylidene)-5H-benzo [5,6] cyclohepta [1,2-b] pyridine is a antihistaminic drug. Desloratadine is an non-sedative antihistaminic drug with selective H1receptor antagonist activity.…”
Section: Introductionmentioning
confidence: 99%
“…Desloratadine is used for relieving the symptoms of allergic rhinitis, pruritus and urticaria. Literature survey reveals that desloratadine alone and in combination with other drugs can be estimated by spectroscopic methods [1][2][3] and RP-HPLC [4][5][6][7]. The chemical structure of desloratadine is shown in the Figure. It is used to treat chronic inflammatory pulmonary conditions, tracheobronchitis, emphysema and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The assay method [1] reported describes the separation of degradation impurities from deslaratadine formed through forced degradation studies, but it was out of scope because it did not separate and determine the impurities. A validated RP-HPLC method has been reported for quantification of desloratadine in pharmaceutical forms [2], a spectophotometric, spectrofluorometric and HPLC method has been reported for determination desloratadine in dosage forms and in human plasma [3] and a LC method has been reported for simultaneous determination of loratadine and desloratadine in pharmaceutical preparations using micro-emulsion as eluent [4], but forced degradation study and impurity details were not reported in these articles [2][3][4]. We have developed a stability-indicating RP-LC method that can separate and determine deslaratadine and its five impurities namely imp-A, imp-B, imp-C, imp-D and imp-E (Fig.…”
Section: Introductionmentioning
confidence: 99%